Votes, Votes, Votes: Explaining the Long Road to Emigrant Enfranchisement in Ireland - Reidy, Theresa (Frontiers in Political Science, 2021)
Enfranchisement of emigrant citizens living outside their home states has been a notable trend in recent decades. While emigrant voting rights are viewed by some as an important part of the wave of suffrage reforms that began in the 1970s, for others they are a contested development that rupture the essence of democracy by breaking the link between citizenship and residence. This article connects insights from the emigrant voting literature with historical institutionalism to argue that the longstanding avoidance of emigrant enfranchisement in the Republic of Ireland was overcome during the Great Recession because of an economic imperative, the need for greater investment from the emigrant community. Diaspora campaigners explicitly linked economic engagement with political rights and the pathway to the policy reform was set. The government gave a commitment in 2017 to hold a referendum to implement the emigrant franchise reform and it is scheduled for 2022, having been delayed by the Covid 19 pandemic.